2021
DOI: 10.1002/jcsm.12867
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis induces interleukin 6, gp130/JAK2/STAT3, and muscle wasting

Abstract: Background Sepsis and inflammation can cause intensive care unit-acquired weakness (ICUAW). Increased interleukin-6 (IL-6) plasma levels are a risk factor for ICUAW. IL-6 signalling involves the glycoprotein 130 (gp130) receptor and the JAK/STAT-pathway, but its role in sepsis-induced muscle wasting is uncertain. In a clinical observational study, we found that the IL-6 target gene, SOCS3, was increased in skeletal muscle of ICUAW patients indicative for JAK/STAT-pathway activation. We tested the hypothesis th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
68
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 96 publications
(70 citation statements)
references
References 43 publications
2
68
0
Order By: Relevance
“…The SuperScript ® First-Strand Synthesis System (Invitrogen™, Life Technologies Corporation, Carlsbad, CA, USA) was used to synthesize 1.5 µg RNA per sample in accordance with the manufacturer’s instructions. Quantitative real-time polymerase chain reaction (qRT-PCR) was performed using Power SYBR ® Green PCR Master Mix (Applied Biosystems) and self-designed primers (for primer sequences see Table S15 ) on a Step-One™ Plus thermocycler (Applied Biosystems, Waltham, MA, USA) using the standard curve method as described recently [ 8 , 58 , 61 , 62 ]. The expression of individual genes was normalized to the geometric mean of the three stably expressed internal control genes mitochondrial ribosomal protein L13 ( Mrpl13 ), importin 8 ( Ipo8 ), and phosphoglycerate kinase 1 ( Pgk1 ) selected from obtained RNA sequencing data and according to previously published work [ 63 ].…”
Section: Methodsmentioning
confidence: 99%
“…The SuperScript ® First-Strand Synthesis System (Invitrogen™, Life Technologies Corporation, Carlsbad, CA, USA) was used to synthesize 1.5 µg RNA per sample in accordance with the manufacturer’s instructions. Quantitative real-time polymerase chain reaction (qRT-PCR) was performed using Power SYBR ® Green PCR Master Mix (Applied Biosystems) and self-designed primers (for primer sequences see Table S15 ) on a Step-One™ Plus thermocycler (Applied Biosystems, Waltham, MA, USA) using the standard curve method as described recently [ 8 , 58 , 61 , 62 ]. The expression of individual genes was normalized to the geometric mean of the three stably expressed internal control genes mitochondrial ribosomal protein L13 ( Mrpl13 ), importin 8 ( Ipo8 ), and phosphoglycerate kinase 1 ( Pgk1 ) selected from obtained RNA sequencing data and according to previously published work [ 63 ].…”
Section: Methodsmentioning
confidence: 99%
“…Previously we showed that MuRF1/Trim63 and atrogin-1/Fbxo32 mRNA and protein expression are increased in the vastus lateralis of critically ill human patients, especially those that were at risk to develop muscle wasting ( 27 ). Both E3 ligases were also upregulated in the tibialis anterior and gastrocnemius and plantaris of mouse models of neurogenic, inflammation- and starvation induced muscle atrophy ( 28 32 ), where their increased expression was associated with the atrophy phenotype and the loss of MyHC. We and others recently summarized the current knowledge about factors and signaling pathways involved in the regulation of E3 ubiquitin ligases relevant for muscle atrophy ( 6 , 33 , 34 ).…”
Section: Mechanisms Of Skeletal Muscle Atrophymentioning
confidence: 99%
“…To cause muscle atrophy, these cytokines bind to their receptors at the myocyte cell surface and activate transcription factors and signaling proteins such as Nuclear Factor-κB (NF-κB), JAK/STAT, SMAD, MAPK, TFEB/TFE3, and IGF/PI3K/AKT to regulate MuRF1/Trim63 and atrogin-1/Fbxo32 expression that in turn mediate muscle atrophy ( 6 , 33 , 34 ). Importantly, in addition to the immune system the skeletal muscle itself contributes to the production and release of acute phase response proteins and proinflammatory cytokines ( 28 , 31 , 32 , 35 ), which may aggravate muscle loss especially during chronic inflammation and sepsis. Although we start to understand the role of protein degradation and its regulation in muscle atrophy only few therapeutic concepts arose from these insights.…”
Section: Mechanisms Of Skeletal Muscle Atrophymentioning
confidence: 99%
See 2 more Smart Citations